IMPLEMENTASI WHATSAPP BUSINESS DAN QRIS SEBAGAI STRATEGI DIGITALISASI TRANSAKSI PADA KONTER PULSA RGS CELL DAN KONTER PULSA RORIZMA DI KABUPATEN BANTUL - Satria Pinayungan Nugroho Putra; Martinus Budiantara (Bajang Institute, 2025)
Transaction digitalization is an essential element in enhancing the efficiency and competitiveness of Micro, Small, and Medium Enterprises (MSMEs). This community service initiative analyzes the implementation of WhatsApp Business and QRIS as transaction digitalization strategies at RGS Cell and Rorizma mobile credit counters in Bantul Regency. Through a one-month training and mentoring program, business owners were provided with an understanding of optimizing WhatsApp Business for communication and marketing, as well as utilizing QRIS to facilitate cashless transactions. The results of the initiative indicate that WhatsApp Business enhances customer interaction through features such as catalogs, automated messages, and conversation labels. Meanwhile, the implementation of QRIS reduces cash payment constraints and increases RGS Cell’s daily transactions by 25% and Rorizma Cell’s daily transactions by 20%. Thus, digitalization through WhatsApp Business and QRIS has been proven to have a positive impact on operational efficiency and customer satisfaction, making it a strategic model for MSMEs in adapting to the digital era